Comparison of a new cephalosporin, BMY 28142, with other broad-spectrum beta-lactam antibiotics. - Kessler, R E (1985)
BMY 28142, a new broad-spectrum semisynthetic cephalosporin, was evaluated in vitro and in vivo in comparison with ceftazidime, cefotaxime, moxalactam, and cefoperazone. The activity of BMY 28142 compared favorably with the activities of the other compounds against both Pseudomonas aeruginosa and Staphylococcus aureus and was somewhat greater against members of the family Enterobacteriaceae. The influence of inoculum size on MICs of BMY 28142 was small for most of the isolates tested, except Enterobacter species. With Enterobacter strains, a marked inoculum effect was found with all of the compounds, and the effect was more pronounced in broth than agar. Still, MICs of BMY 28142 in broth did not exceed 16 micrograms/ml. Of 37 Enterobacteriaceae strains resistant to one or more of the comparison beta-lactams, none were resistant, at a low inoculum size (10(4) CFU), to BMY 28142, compared with 3 for moxalactam, 18 for ceftazidime, 23 for cefotaxime, and 34 for cefoperazone; at an inoculum size of 10(6) CFU, the number of resistant strains was 12, 17, 25, 34, and 37, respectively. Binding to human serum proteins approximated 19%. Recovery of 73% of the drug in mouse urine indicated good bioavailability. The in vitro profile was sustained in vivo by the results obtained with experimental infections in mice. BMY 28142 was as effective as ceftazidime against systemic infection with P. aeruginosa and as effective as cefotaxime against systemic infection with S. aureus. Overall, infections with 18 of 20 strains representing nine genera were responsive to BMY 28142 at doses equivalent to or lower than those of the most effective of the comparison compounds.